Comparison of the Characteristics and Prognosis Between Very Young Women and Older Women With Breast Cancer: A Multi-Institutional Report From China - Yang, Yaping; Wei, Weidong; Jin, Liang; He, Haiyan; Wei, Mengna; Shen, Shiyu; Pi, Hao; Liu, Zhiqin; Li, Hengyu; Liu, Jieqiong (Frontiers in Oncology, 2022)
Purpose: Very young breast cancer (<=35 years) remains limitedly understood. We aimed to assess the clinicopathological characteristics, molecular subtype and treatment distribution and prognosis of these young patients compared to patients over 35 years. Methods: We retrospectively analyzed non-metastatic female breast cancer cases treated at three Chinese academic hospitals between January 1, 2008 and December 31, 2018. Local recurrence-free survival (LRFS), disease-free survival (DFS) and overall survival (OS) were compared between different age groups, and stratified with distinct molecular subtypes. Results: 11671 women were eligible for final analyses. 1207 women (10.3%) were <= 35 years at disease onset. Very young breast cancer women were more likely to be single or childless, have higher-grade disease, more probability of lymphovascular invasion (LVI) in tumor and triple-negative subtype, and be treated by lumpectomy, chemotherapy especially more anthracycline and paclitaxel-based chemotherapy, endocrine therapy plus ovarian function suppression (OFS), anti-HER2 therapy and/or radiotherapy than older women (P<0.05 for all). Very young women had the lowest 5 years LRFS and DFS among all age groups (P<0.001 for all). When stratified by molecular subtype, very young women had the worst outcomes vs. women with 35~50 years group or those >50 years group for Hormone receptor positive (HR+)/ Human epidermal growth factor receptor 2 negative (HER2-) subtype, including LRFS, DFS and OS (P<0.05 for all). In terms of LRFS and DFS, multivariate analyses showed similar results among different age groups. Conclusion: Our study demonstrated that very young women with breast cancer had higher-grade tumors, more probability of LVI in tumor and more triple-negative subtype, when compared with older patients. They had less favorable survival outcomes, especially for patients with HR+/HER2- subtype.